Friedrich Hölderlin or Emanuele Severino? The Sacral Dimension of Nature in the Context of Modern Technology - Kobylinski, Andrzej (Studia Ecologiae et Bioethicae, 2024)
The main purpose of inquiries undertaken in this study is to present a synthesis of the views of the German poet Friedrich Hölderlin and the Italian thinker Emanuel Severino on nature and technology, and to analyze the contemporary manifestations of the re-sacralization of nature in many ecological currents, as discussed in her studies by the French philosopher Chantal Delsol. For Hölderlin, nature is never limited to being an empirical object of scientific investigation. It is a divine reality that does not undergo change. It is a space inhabited by the sacred. Nature constitutes the sacred All, beyond which nothing else exists. Severino, in turn, analyzes the impact of modern technology on nature, man and the entire existing world. He believes science and modern technology have become an extremely effective tool of man’s dominion over the natural world. The Italian philosopher says that today the human will to power applied to nature leads to its objectification and desacralization. Delsol, on the other hand, points out that throughout Western culture we are now witnessing the birth of a new religion of nature, which is a modern form of ancient paganism. The analyses performed demonstrate that, on the one hand, nature is currently being subjected to profound changes due to science and technology, while on the other – its former sacral character is being restored, forming the foundation of a new form of religiosity.